A PRAGMATIC ANALYSIS FRAMEWORK FOR THE DESCRIPTION OF MODALITY USAGE IN ACADEMIC ENGLISH CONTEXTS - Piqué, Jordi; Posteguillo, Santiago; Andreu-Besó, J.Vicent (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In our pragmatic approach to research articles (RAs), we take a look at one of the main characteristics of academic writing: the use of modalized statements. Modalization, in the form of modal verbs, has been extensively studied by ESP researchers and practitioners. Most of their studies, however, have slightly touched upon the distinction between epistemic modality, which questions the certainty or probability of a statement, and deontic modality, which lays obligations or gives permission to the audience. This dichotomy is an important tool to describe disciplinary variations in academic and professional writing. We contend that different disciplines favor different types of modality. Results in this study indicate that health science RAs mostly use epistemic modality, whereas literary criticism RAs combine the use of both epistemic and deontic modality.